2020
DOI: 10.1007/978-3-030-64697-4_11
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal (In)justice in Digital Platforms: An Analysis of Food-Delivery Platforms in South India

Abstract: With on-demand labour and location-based services becoming increasingly common, this paper explores the complex social justice impact of spatial and temporal elements of digital platforms. A conceptual framing of 'spatiotemporal justice' is proposed to explore the consequences of algorithmic control of space and time experienced by workers. An interpretive case-study is built focusing on work practices of food-delivery platforms in the south Indian city of Chennai. The qualitative methods used include semi-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The authors propose that in the gig economy, algorithms pose spatiotemporal systems of inequality and neo-liberal precarity. This is consistent with Krishna's (2020) findings that spatiotemporality on digital platforms is intertwined with social justice in three ways: the spatiotemporal trade-offs between risk and stress against the benefits of employment, concerns with imperfect digital representations, and an asymmetry of power and information. These outcomes pose spatiotemporal injustice for platform workers, particularly those in the global South.…”
Section: Algorithmic Management In the Gig Economysupporting
confidence: 89%
“…The authors propose that in the gig economy, algorithms pose spatiotemporal systems of inequality and neo-liberal precarity. This is consistent with Krishna's (2020) findings that spatiotemporality on digital platforms is intertwined with social justice in three ways: the spatiotemporal trade-offs between risk and stress against the benefits of employment, concerns with imperfect digital representations, and an asymmetry of power and information. These outcomes pose spatiotemporal injustice for platform workers, particularly those in the global South.…”
Section: Algorithmic Management In the Gig Economysupporting
confidence: 89%
“…As an increasingly large and diverse population of workers chooses to join the gig economy and build their careers in a digital workplace, it is critical for platforms to create a culture that embraces fairness (C2) (Chibanda et al, 2022; Krishna, 2020). Prior research found that many rideshare drivers suffered from unfair labor practices because they were defined by the platform as independent contractors (Fleitoukh & Toyama, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The opaque algorithmic governance raises issues about fairness, accountability, and the right of workers to contest decisions that affect their liveli hoods. Research by [41] in the domain of food delivery services in South India revealed the spatial and temporal injustices inherent in digital platforms. These platforms often reinforce existing power dynamics and inequalities, resulting in unequal access to opportunities and resources.…”
Section: «The Adoption Of Digital Platforms Enables the Development O...mentioning
confidence: 99%